2019
DOI: 10.1039/c9fo01387c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liver gene expression by RNAseq and PCR analysis after 8 weeks of feeding soy protein isolate- or casein-based diets in an obese liver steatosis rat model

Abstract: Differential expression of genes provides insight into fundamental mechanisms associated with the ability of soy protein isolate to attenuate liver steatosis in genetically obese rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 82 publications
2
6
0
Order By: Relevance
“…However, the precise mechanisms that lead to SPImediated attenuating liver steatosis is not completely understood. To better understand fundamental mechanisms by which SPI attenuated NAFLD, we conducted global transcriptomic (RNAseq) analysis on liver tissue obtained from obese rats fed the SPI-and CAS-based diets for 8 weeks (13). The results of this study indicated gene expression that would promote anti-inflammatory activities in SPI-fed rats and inflammatory activities in CAS-fed rats, which is consistent with the observation of reduced liver steatosis in SPI-fed rats (12).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, the precise mechanisms that lead to SPImediated attenuating liver steatosis is not completely understood. To better understand fundamental mechanisms by which SPI attenuated NAFLD, we conducted global transcriptomic (RNAseq) analysis on liver tissue obtained from obese rats fed the SPI-and CAS-based diets for 8 weeks (13). The results of this study indicated gene expression that would promote anti-inflammatory activities in SPI-fed rats and inflammatory activities in CAS-fed rats, which is consistent with the observation of reduced liver steatosis in SPI-fed rats (12).…”
Section: Introductionsupporting
confidence: 77%
“…Colony stimulating factor 2 (CSF2) ( Table 3A and Figure 6A) or granulocyte-macrophage colony-stimulating factor (GM-CSF) was predicted to be inhibited in SPI-fed rats at 16 weeks (activation z score = −2.29). Its receptor, CSF2 receptor beta (CSF2RB) was found to be down-regulated at 8 weeks on the SPI diet (13). CSF2 is a cytokine involved in inflammatory response that modulates the production and differentiation of macrophages and granulocytes (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…This study used the methods described in the studies by Hakkak et al ( 29 ) and Kozaczek et al ( 32 ), and the description of the methods partly reproduces their wording ( 29 , 32 ). The protocol for this study (code number 3242) was approved by the Institutional Animal Care and Use Committee at the University of Arkansas for Medical Sciences (IACUC) on December 6, 2011.…”
Section: Methodsmentioning
confidence: 99%
“…The methods for RNA extraction from the liver samples and the pipeline followed to generate the RNAseq data are described in Kozaczek et al ( 32 ). More than 1,200 transcripts were differentially expressed (>1.3-fold difference and P < 0.05) and later evaluated with Ingenuity Pathway Analysis program (IPA, Qiagen, CA) to help in the analysis and understanding of the global gene expression data.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Narp protein has been reported to be present in rat testes but not in other peripheral tissues (O'Brien et al, 1999). However, recently, it has been shown that Narp protein is expressed in peripheral tissue such as the liver (Kozaczek et al, 2019).…”
Section: Expression Pattern and Function Of Np2mentioning
confidence: 98%